Are sleep disturbances causally linked to the presence and severity of psychotic-like, dissociative and hypomanic experiences in non-clinical populations? A systematic review. (June 2018) - Barton, Jack; Kyle, Simon D.; Varese, Filippo; Jones, Steven H.; Haddock, Gillian
Highlights: Sleep disturbances are associated with all experiences reviewed. Paucity of research examining circadian rhythms in psychotic-like experiences. Limited research addressing causal ordering between sleep and experiences studied. Abstract: The present review aimed to 1) identify what sleep disturbances co-occur alongside psychotic-like, dissociative and hypomanic experiences; 2) assess the strength of potential associations between the severity of sleep disturbances and of the experiences studied; and 3) appraise evidence for a causal link. MedLine and PsycInfo were searched and 44 studies were deemed eligible. Results showed that insomnia was associated with all individual psychotic-like, dissociative and hypomanic experiences reviewed (effect size range: small-to-large). Parasomnias were associated with all psychotic-like experiences; however, there was evidence of variation in magnitude between individual experiences. An eveningness chronotype was associated with dissociative and hypomanic experiences, and circadian dysrhythmia was found alongside hypomania but not the other experiences reviewed. Finally, experimental sleep manipulation studies revealed a potential causal link between sleep loss and psychotic-like and dissociative experiences, although size and consistency of effects varied by specific experience. Future research, using experimental manipulations of sleep to address putative mechanisms, will enable questions of causality to be answered with more confidence.